Memento : algunos recuerdos es mejor olvidarlos - Nolan, Christopher, 1970-; Moss, Carrie-Anne; Pearce, Guy, 1967-; Nolan, Johnatan; Pantoliano, Joe (Avalon, 2012)
A man creates a strange system to help him remember things; so he can hunt for the murderer of his wife without his short-term memory loss being an obstacle.